Activin A: a novel urinary biomarker of renal impairment in multiple myeloma. Issue 5 (31st May 2019) - Iriuchishima, Hirono; Maeshima, Akito; Takahashi, Shunsuke; Ishizaki, Takuma; Yokohama, Akihiko; Tsukamoto, Norifumi; Saitoh, Takayuki; Murakami, Hirokazu; Handa, Hiroshi
Abstract : Renal impairment (RI) is a common complication of multiple myeloma (MM) that significantly affects treatment efficacy and mortality. However, no useful biomarkers for early detection of renal damage in MM exist. Reports indicate that activin A, a multifunctional cytokine of the TGF-β superfamily, is involved in the development and progression of various kidney diseases. In the present study, we measured urinary activin A levels in patients with newly diagnosed MM (NDMM) ( n =41), smoldering MM (SMM) ( n =10), and monoclonal gammopathy of undetermined significance (MGUS) ( n =28), including monoclonal gammopathy of renal significance (MGRS), and assessed the correlation between urinary activin A and several clinical parameters. Urinary activin A, undetectable in healthy volunteers, was significantly increased in NDMM patients but not in patients with SMM and MGUS (97.3, 25.0, and 6.61 mg/gCr, respectively, P <0.05). In all patients with NDMM, urinary activin A levels were significantly reduced after initial treatment regardless of the therapy regimen. There was a significant correlation of urinary activin A with spot urinary protein level ( P <0.001) and serum M-protein ( P =0.029) but not with estimated glomerular filtration rate (eGFR), serum creatinine (Cr), N-acetyl-glucosaminidase (NAG), and serum activin A level. Histological analysis using renal biopsy samples revealed that activin A, which was absent from normal kidneys, was detected in the renal tubular cells of patients with MGRS. These data suggest that urinary activin A reflects tubular injury in MM and might aid the early detection of RI in plasma cell neoplasms.